2007
DOI: 10.3846/16111699.2007.9636179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Business Strategic Decisions Under Changing Environment Conditions

Abstract: A problem of strategic decisions evaluation under changing environment conditions is analyzed in this article. In the context of these conditions the use of scenarios’ method, integrating scenarios formation into strategic decisions evaluation process, is perspective. The combination of multicriteria evaluation and scenarios’ method allows versatile evaluation of strategic decisions in aspects of usefulness and viability regarding perspective environment situations. A universal scenarios formation technology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Experience has shown that companies do their best when they focus their process-improvement efforts on a manageable number of process areas or those business decisions that require increasingly sophisticated effort as the organization improves (Ladley 2010;Yuan et al 2009;Zinkevičiūtė 2007;Humphrey 1989). A maturity level is a defined evolutionary scale of process improvement.…”
Section: Organization Process Maturity: a Review Of The Literaturementioning
confidence: 98%
“…Experience has shown that companies do their best when they focus their process-improvement efforts on a manageable number of process areas or those business decisions that require increasingly sophisticated effort as the organization improves (Ladley 2010;Yuan et al 2009;Zinkevičiūtė 2007;Humphrey 1989). A maturity level is a defined evolutionary scale of process improvement.…”
Section: Organization Process Maturity: a Review Of The Literaturementioning
confidence: 98%
“…In Goodwin and Wright (2001), a multi-attribute value function, based on a subjective 100-0 value scoring, is integrated into a scenario-based framework to evaluate the robustness of different strategies. Similar frameworks have been proposed, based on multi-attribute scoring functions, to assess the impact of different scenarios on each strategy proposed (Ram et al, 2011;Ram and Montibeller, 2013;Montibeller et al, 2006;Zinkevičiūte, 2007;Schroeder and Lambert, 2011;Karvetski et al, 2011).…”
Section: Scenario-based Strategic Designmentioning
confidence: 99%
“…Following this field of research, the scientific investigation of literature makes a point about the application of strategic management: Vaitkevicius, S. (2007); Slater, Olson & Hult (2006) demonstrate the moderating influence of strategic orientation on the strategy and formation capabilityperformance relationship; Gudonavicius, Bartoseviciene, & Saparnis (2009) analyse imperatives for enterprise strategists; Kubrak, Koval, Kavaliauskas &Sakalas (2009) discuss organizational structure forming problems in modern industrial enterprise; Tijunaitiene, Neverauskas (2009) consider activation of participation motivation directed towards agents and present a conceptual model. Diskiene, Galiniene & Marcinskas, (2008) presented a strategic management model for economic development; Zinkeviciute (2007) analyze a problem of strategic decisions evaluation under changing environment conditions.…”
Section: Crisis Is the Event Or Situation Related With Threat Which Gmentioning
confidence: 99%